Design and Implementation of Standard Operating Procedures to Improve Production Quality in Small-Scale Coffee Roasteries: Evidence from a Robusta Processing SME - Puttileihalat, Anatasya Litisya; Cahyaningrum, Deltaningtyas Tri (CV. SPDFHarmony, 2026)
Background: Small-scale agroindustry enterprises often face operational inefficiencies due to the absence of standardized production procedures. In coffee processing SMEs, inconsistent work practices may lead to product defects, reduced productivity, and unstable product quality. Macro Coffee Roastery, a small-scale coffee processing enterprise in Jember, Indonesia, experienced similar issues, particularly in the production of robusta coffee, where the lack of formal Standard Operating Procedures (SOPs) contributed to quality inconsistencies and operational errors during production activities. Aims: This study aims to design and implement Standard Operating Procedures for the robusta coffee production process and to evaluate the effectiveness of the SOP implementation in improving production quality within a small-scale coffee roasting enterprise. Methods: The research employed a mixed-method approach combining qualitative and quantitative techniques. Data were collected through field observations, interviews with production workers, and documentation of product defect rates before and after SOP implementation. The production process analyzed includes raw material preparation, roasting, cooling (tempering), grinding, and packaging. Quantitative evaluation of the SOP implementation was conducted using the Chi-Square test to examine changes in defect levels. Result: The study produced a comprehensive SOP framework covering five key stages of the robusta coffee production process. Following the implementation of the SOP, the level of product defects decreased significantly, indicating improved consistency and operational control in the production system. Conclusion: The findings demonstrate that the introduction of structured Standard Operating Procedures can substantially enhance operational discipline, process consistency, and product quality in small-scale coffee agroindustries. SOP implementation provides clear work guidelines for employees, reduces procedural deviations, and supports more systematic production management. For small and medium enterprises in the agroindustry sector, the development of standardized production systems represents an effective managerial strategy to strengthen quality assurance and operational reliability. Furthermore, the adoption of SOP-based production management may contribute to improving competitiveness, ensuring product consistency, and supporting sustainable growth in emerging coffee processing enterprises